Boganmeldelser - Peter Garde; Maria Kaspersson; Charlotte Mathiesen Bech; Peter Kramp; Lars Bo Langsted; Kjersti Ericsson; Paul Larsson; Stig Winge; René Dejbjerg Pedersen (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews